O eu no enunciado do outro: a voz do intérprete durante o ato interpretativo do par linguístico Libras/Língua Portuguesa - Oliveira, Carlos Alberto Matias de (2020)
This master thesis has as general objective to identify what effects of senses are produced in and by the neutrality discourses that cross the field of translation and interpretation of Libras to portuguese language and, consequently, their protagonist: the translator and interpreter of sign language (LIBRAS / Portuguese) (TILSP). I established two specific objectives: the first is to identify what representations are created in and by the institutional documents regulating TILSP professionals, analyzing how institutional documents weave links on society, working as a gear of (re)production of discourses. The second specific objective is to establish a dialogue between the questions raised in the process of building laws related to the translation and interpretation, and the reality of TILSP's work. On this aim, I join the Applied Linguistic of the 21st century (MOITA LOPES, 2006; PENNYCOOK 1998; FABRÍCIO, 2006), understanding that in this area the research haves an inseparable relationship with life, close to the core of language functioning, that is, the subject. I performed a documentary analysis on documents from laws and unions of TILSPs, to identify how they built the TILSP representation and points to social marks, guiding the relation between these professionals and the others into the tradutory processes. I also conduct narrative interviews with TILSPs and deaf students, establishing a dialogue between discourses arising from the documentary analysis and the reality on TILSP's work. I found that the analyzed excerpts prefigure the TILSP as a lesser object transporting meanings between languages. Such discourses have presented this professional as a non-person. In addition, is clear that the discourses of neutrality, which are ideologically oriented, have also operated on TILSP's body (through prohibition of the use of accessories and clothes considered non-neutrals during the translation act) with the intention of erasing the TILSP professional from his workplace. The discourses of neutrality have been used in discursive practices to silence and subordinate the TILSPs, moving them to the margins of the places where they are located to prevent them from participate in the classes during their exercise of the profession, through comments or opinions. Agreeing with Albres (2015), I consider that TILSP, in educational contexts, assumes the role of educator, participating in the teaching/learning process. Furthermore, I point out that neutrality has been used, in the field of translation, as a way of (re)production of relations of power and domination with the use of language signs that are oringinated from discourses of colonialism. I hope that this work can contribute to the field of the Translation and Applied linguistics, considering that these results can contribute for the transformation of the social relations between TILSP professionals and the other(s) in the interlocutive process.